Polysémie de HOW dans la King James Version - Mathilde Pinson (Anglophonia)
This paper aims at analyzing the various functional and semantic values attributed to the morpheme how in the King James Version of the Bible (KJV), some of which are not prototypical (complementizer, causal interrogative adverb, interrogative pronoun and adverbial relative). In view of the complex semantic and functional network of how, it is necessary first to establish what decoding problems were experienced by the readers. As will be shown, almost each type of how can be misinterpreted in some contexts and quite often only the comparison with other English versions of the Bible, or with the Latin, Greek or Hebrew versions, enables one to interpret the text accurately. The translators seem to have been aware of the interpretation difficulties that this polysemy entailed, because they often managed to limit them by adding material to the communicatively deficient morpheme (e.g. how that, how is it that). The origin of the two main non-prototypical uses of how will then be examined, and it will be demonstrated that conjunctive how is endogenous, while the source of causal how is mainly exogenous. Finally, it will be shown that the causal value of how has not disappeared altogether from Present-Day English, contrary to what the Oxford English Dictionary indicates, and it will be hypothesized that the use of causal how in Scottish Vernacular English is related to that in the KJV.